Pengaruh Inklusi Keuangan, Sistem Informasi Akuntansi, dan Kompetensi Sumber Daya Manusia Terhadap Kinerja UKM di Kota Bengkulu - Rio Akbar, Muhammad; Coryanata, Isma (CV. Lafadz Jaya, 2024)
This study aims to analyze the impact of three factors—financial inclusion, accounting information systems (AIS), and human resource competencies—on the performance of Small and Medium Enterprises (SMEs) in Bengkulu City. Using the Resource-Based View (RBV) theory, this research identifies how these factors contribute to improving SME performance. Financial inclusion provides easier access to financial services, supporting business growth, while the implementation of effective AIS enhances the accuracy of reporting and decision-making. Human resource competencies, including knowledge, skills, and motivation, also play a crucial role in the success of SMEs. The findings show that these three factors significantly and positively influence SME performance, reflected in increased sales, profitability, and market competitiveness. This study contributes to the RBV theory by demonstrating that these factors serve as valuable resources that support competitive advantage for SMEs.